Occurrence, effects and environmental risk of antifouling biocides (EU PT21): Are marine ecosystems threatened? - de Campos, Bruno Galvão [UNESP]; Figueiredo, Joana; Perina, Fernando [UNESP]; Abessa, Denis Moledo de Souza [UNESP]; Loureiro, Susana; Martins, Roberto (Taylor & Francis, 2021)
This review presents a comprehensive compilation of toxicological and environmental data, further used to assess the ecological risk (ERA) of the 11 EU approved antifouling biocides (PT21). Diuron, chlorothalonil, DCOIT, and pyrithiones are amongst the most toxic biocides toward producer species, while, CuSCN, medetomidine, and zineb showed higher toxicity toward consumers. In addition, medetomidine, CuSNC, zineb, Cu2O, and chlorothalonil are up to 400-fold more toxic to non-target organisms than target organisms highlighting their potential threat for marine ecosystems. Biocides hazard, which was assessed based on the marine PNECprobabilistic for biocides having enough and reliable ecotoxicological data, can be summarized in the following order: ZnPT (more hazardous) > CuPT > DCOIT > diuron > chlorothalonil > dichlofluanid > tolylfluanid. For the remaining biocides, the marine hazard was calculated based on the PNECdeterministic as follows: CuSCN (more hazardous) > Cu2O > medetomidine > zineb. The risk assessment indicates that the following biocides poses risk (quotient >1) for the coastal ecosystems: DCOIT, diuron, dichlofluanid, chlorothalonil, CuSCN, Cu2O, medetomidine and zineb. In order to protect the services and functions of coastal environments, a systematic and continuous monitoring of these biocides in coastal areas are highly recommended. Current regulatory framework and the replacement of state-of-the-art biocides by safer alternative is also critically discussed.
Keywords: Biofouling; hazard assessment; predicted no effect concentration (PNEC); regulation; risk assessment; species sensitivity distribution (SSD)